9-2(x+4)=8(3-x)+1

Simple and best practice solution for 9-2(x+4)=8(3-x)+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9-2(x+4)=8(3-x)+1 equation:


Simplifying
9 + -2(x + 4) = 8(3 + -1x) + 1

Reorder the terms:
9 + -2(4 + x) = 8(3 + -1x) + 1
9 + (4 * -2 + x * -2) = 8(3 + -1x) + 1
9 + (-8 + -2x) = 8(3 + -1x) + 1

Combine like terms: 9 + -8 = 1
1 + -2x = 8(3 + -1x) + 1
1 + -2x = (3 * 8 + -1x * 8) + 1
1 + -2x = (24 + -8x) + 1

Reorder the terms:
1 + -2x = 24 + 1 + -8x

Combine like terms: 24 + 1 = 25
1 + -2x = 25 + -8x

Solving
1 + -2x = 25 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
1 + -2x + 8x = 25 + -8x + 8x

Combine like terms: -2x + 8x = 6x
1 + 6x = 25 + -8x + 8x

Combine like terms: -8x + 8x = 0
1 + 6x = 25 + 0
1 + 6x = 25

Add '-1' to each side of the equation.
1 + -1 + 6x = 25 + -1

Combine like terms: 1 + -1 = 0
0 + 6x = 25 + -1
6x = 25 + -1

Combine like terms: 25 + -1 = 24
6x = 24

Divide each side by '6'.
x = 4

Simplifying
x = 4

See similar equations:

| -14.3=-1.8-3D | | 5-22=5x-4-4x | | 9×1/1000 | | 14x+9y=18p | | -150=-6(1-6x) | | 15u=135 | | x-2x=5+x | | 20th-8x=x-8 | | y=cos3/4x | | .2x+x^2=0 | | 5x+10y=166 | | 9y-7+18=2 | | (.2+x)x=0 | | (2.3x+25)=(5.8x+11) | | (.2+x)x=x^3 | | X-98=258 | | -8m-[3m(11+4m)+2]=9m | | 7y-42(0)+7=0 | | -3=6n-5n | | -69+11x=x+61 | | w-2-3h=52 | | 8x-14=(x^2)+1 | | 4x+-4x=-1x+-1 | | 61=4x-13 | | -2(x-4)(x+3)=0 | | log^3(x)=log^9(3*x+18) | | 1b=-42 | | 12x+8y=138 | | (X+11)(x+3)=240 | | x*(2x+7)=460 | | 1/3*2.25 | | (3z-5)(3z+15)=0 |

Equations solver categories